Blind multiuser detection for code-hopping DS-CDMA signals in asynchronous multipath channels. - Tugnait, J.K.
Blind detection of a desired user's signal in a code-hopping (CH) direct sequence code-division multiple access (CDMA) system is considered. In CH CDMA systems each user switches between a predetermined set of short-code sequences. A user signal in such systems may be treated as the superposition of several virtual short-code signals. A code-constrained inverse filter criterion (IFC)-based blind detector for short-code CDMA signals in asynchronous multipath channels to detect a desired user's signal was recently presented by Tugnait and Li (2001). A novel approach combining the code-constrained IFC and a penalty function is proposed to simultaneously extract all virtual users associated with a given CH user. Global minima of the proposed cost function are analyzed. An extension of an existing subspace-based approach is also investigated. An illustrative simulation example is provided where the proposed algorithm is compared with a clairvoyant matched filter receiver, two linear minimum mean-square error (MMSE) receivers with channels known, and the subspace-based approach.
Keywords: MMSE receivers; Asynchronous multipath channels; Blind multiuser detection; Code-hopping DS-CDMA signals; Cost function; Direct sequence-code division multiple access; Intersymbol interference; Inverse filter criterion; Matched filter receiver; Minimum mean square error; Multiaccess communication; Multipath channels; Penalty function; Short-code sequences; Signal detection; Spread spectrum communication; Virtual users